Gunboat diplomacy : Turkey, USA and the advent of the cold war - İnanç, Gül. (2013)
This article aims to re-evaluate the visit of the battleship USS Missouri to Turkey on 5–6 April 1946, to ascertain whether or not it might be considered an early attempt on the part of the United States to challenge the Soviet Union. Greater historical clarity than previously possible has been achieved through the use of hitherto unreleased documents from the archives of the Ministry of Foreign Affairs of the Turkish Republic. Moreover, this article aims to achieve a more balanced and comprehensive analysis by integrating the systemic factors with the actions of crucial actors at the individual level based on new archival evidence. By doing this, the main argument emerges whereby the United States displayed its power against the Soviets via the visit of the USS Missouri only in hindsight; while the decision to send home the exhumed body of the late Turkish ambassador Mehmet Münir Ertegün was the action of an individual. However, due to the advent of the Cold War, the dynamics shaping Turkey's search for security and ultimately the containment policy of the United States, has loaded the event with more meaning than was originally intended, turning a ‘diplomatic courtesy’ into ‘gunboat diplomacy’.